Asupan Lemak Jenuh dengan Tekanan Darah pada Lansia Wanita - Nida Amalia; A'immatul Fauziyah (Jurnal Ilmiah Kesehatan (JIKA), 2021)
The population of the elderly people is increasing from time to time and there is a change in the diseases pattern from infectious diseases to degenerative diseases. One of degenerative diseases that frequently occur in the elderly people is an increased blood pressure or hypertension. This study aims to determine the relationship between saturated fat intake and blood pressure in elderly women. This type of research was quantitative using a cross sectional approach. Samples were taken with a total sampling technique of 40 subjects. Processing data was using The Pearson correlation test. Based on the results of the analysis test, there was no relations between saturated fat intake with systolic blood pressure and diastolic blood pressure (p-value=0,183 and 0,333). This was because many factors affect blood pressure. The conclusion of this study was that there was no relationship between saturated fat intake with systolic blood pressure and diastolic blood pressure.